Palladium supported on magnesium hydroxyl fluoride: an effective acid catalyst for the hydrogenation of imines and N-heterocycles - Kokane, Reshma; Corre, Yann; Kemnitz, Erhard; Dongare, Mohan K.; Agbossou-Niedercorn, Francine; Michon, Christophe; Umbarkar, Shubhangi B. (New Journal of Chemistry, 2021)
Palladium catalysts supported on acidic fluorinated magnesium hydroxide Pd/MgF2-x(OH)(x) were prepared through precipitation or impregnation methods. Applications to the hydrogenation of various aldimines and ketimines resulted in good catalytic activities at mild temperatures using one atmosphere of hydrogen. Quinolines, pyridines and other N-heterocycles were successfully hydrogenated at higher temperature and hydrogen pressure using low palladium loadings and without the use of any acid additive. Such reactivity trend confirmed the positive effect of the Bronsted and Lewis acid sites from the fluorinated magnesium hydroxide support resulting in the effective pre-activation of N-heterocycle substrates and therefore in the good catalytic activity of the palladium nanoparticles during the hydrogenations. As demonstrated in the hydrogenation of imines, the catalyst was recycled up to 10 times without either loss of activity or palladium leaching.